2011
DOI: 10.5472/mmj.2011.02048.1
|View full text |Cite
|
Sign up to set email alerts
|

Residents' Professional Satisfaction And Its Effects On Their Lives

Abstract: Amaç: Çalışmada, Dokuz Eylül Üniversitesi Tıp Fakültesi Hastanesinde ihtisas yapan asistan hekimlerin uzmanlık tercihleriyle ilgili memnuniyetlerinin, yaşam ve eğitim koşullarının değerlendirilmesi amaçlanmıştır.Gereç ve Yöntem: Bu kesitsel çalışmada; demografik bilgiler ile Minnesota İş Doyum Ölçeği'nden oluşan 51 soruluk anket yüz yüze görüşme yöntemiyle çalışmaya katılmayı kabul eden 252 asistan hekime uygulanmıştır.Bulgular: Katılımcıların %92,1'i çalışmakta oldukları bölüme isteyerek başlamıştı. Uzmanlık … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The reason for this may be that surgery patients may be stressful and have greater expectations from their physicians or the surgeon's malpractice concerns, intense working conditions, and the pressure of the masterapprentice relationship dominant in surgery clinics may also increase the frequency of negative interactions. In a study conducted in the Hospital of Dokuz Eylül University Medical Faculty a work satisfaction survey was applied to residents and it was reported that work satisfaction was higher among internal medicine and internal medicine branches than the surgical branches (40).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be that surgery patients may be stressful and have greater expectations from their physicians or the surgeon's malpractice concerns, intense working conditions, and the pressure of the masterapprentice relationship dominant in surgery clinics may also increase the frequency of negative interactions. In a study conducted in the Hospital of Dokuz Eylül University Medical Faculty a work satisfaction survey was applied to residents and it was reported that work satisfaction was higher among internal medicine and internal medicine branches than the surgical branches (40).…”
Section: Discussionmentioning
confidence: 99%
“…The department assessment score, institution assessment score and the total satisfaction score for the residency education of this study participants aged 36 and over were higher than the participants in the age groups 24-29 and 30-35. Considering the literature, although there are studies (21,22) with no relationship between age and job satisfaction, there are also studies showing that there is a relationship between age and job satisfaction (23,24). Depending on the increase in professional experience in later years, there is an increase in job satisfaction and residency education satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…", despite being a common reason in the literature. [3][4][5]7,13,14 Earlier studies showed that gender is an important factor for specialty preference. 3,[14][15][16][17][18] It is known that men are more likely to choose surgical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…3 In Turkey, studies have shown that the main factors that affect specialty preference are personal skills, personal traits, working conditions, career opportunities, income satisfaction, work and private life balance, public opinion about the specialty and professors' attitudes. [4][5][6][7] Personality traits found associated with career choice many times. 8,9 Personality trait phenotypes have been classified differently by many scientists throughout the years.…”
Section: Introductionmentioning
confidence: 99%